Psychometric properties of the Danish version of the Caregiver Burden Scale: Investigating predictors and severity of burden after stroke, spinal cord injury, or traumatic brain injury - Anne Norup; Pernille Langer Soendergaard; Mia Moth Wolffbrandt; Fin Biering-Sørensen; Juan Carlos Arango-Lasprilla; Frederik Lehman Dornonville de la Cour (Medical Journals Sweden, 2024)
Objective: To investigate (i) psychometric properties of the Danish version of the Caregiver Burden Scale, (ii) predictors of burden in caregivers of persons with stroke, spinal cord injury, or traumatic brain injury, and (iii) severity of caregiver burden, and compare level of severity of burden in caregivers of persons with stroke, spinal cord injury, or traumatic brain injury. Design: Cross-sectional study. Participants: Pooled sample of 122 caregivers. Methods: Psychometric properties including internal consistency, floor and ceiling effects, inter-item and item-total correlation were investigated using the Caregiver Burden Scale. Severity of burden was compared using Fisher's exact test and ANOVA, and predictors of burden were investigated using multiple linear regression models. Results: The total burden score exhibited good internal consistency (α = 0.93), with no floor or ceiling effects. Longer time as a caregiver was a significant predictor of higher total score. The majority (52.2%) reported a low level of caregiver burden (below cut-off of 2.00). Mean scores on the Caregiver Burden Scale were not significantly different among caregivers across diagnostic groups. Differences were found when comparing spinal cord injury caregivers with brain injury caregivers (traumatic brain injury and stroke, collectively), χ2(2) = 6.38, p = 0.04, as spinal cord injury caregivers were more likely to report low levels of burden. Conclusion: Good psychometric properties were reported, and most caregivers reported a low level of burden, and longer time as a caregiver was associated with higher burden. Consequently, the Caregiver Burden Scale is a valid measure to use when measuring burden in caregivers of stroke, spinal cord injury, and traumatic brain injury patients.